Financial Mechanisms and Tools for Supporting the Sustainable Development of Small Businesses in the Construction Industry Within Local Communities - Synchak, Viktor; Vasylenko, Kateryna (Herald of Economics, 2026)
In today’s environment, small businesses in the construction industry require ongoing financial support. This underscores the need for an appropriate financial mechanism and its tools to regulate and ensure financial support for the sustainable development of small businesses in local communities.The purpose of the study is to reveal the essence and justify the principles for improving the financial mechanism and tools to support the sustainable development of small construction businesses in local communities.The following methods were used in this research article: generalization, used to compare approaches to revealing the essence of the financial mechanism; tabular analysis – to visualize analytical and calculated indicators; comparative analysis – to identify deviations in indicators; systems analysis – to analyze the dynamics of equity capital; and analysis and synthesis – t o formulate conclusions and recommendations.It has been established that the financial mechanisms and instruments for supporting the sustainable development of small businesses in local communities do not shield entities in the construction industry from vulnerability to internal and external factors. It is argued that the financial mechanism and instruments for supporting the sustainable development of small businesses in the construction sector within local communities should be directed toward regulatory and enabling processes, with the possibility of introducing new tools for attracting financial resources through special-purpose bonds, with state assistance in organizing their issuance.Prospects for further research lie in the need for an in-depth study of the tax burden, including an analysis of discrepancies between paid and accrued tax liabilities.